This I believe : the personal philosophies of remarkable women and men - Allison, Jay; Gediman, Dan; Gregory, John, 1964-; Merrick, Viki (H. Holt, 2006)
Based on the National Public Radio series of the same name, This I believe features eighty essayists... from the famous to the unknown... completing the thought that begins the book's title.